2020
DOI: 10.3390/ijerph17217811
|View full text |Cite
|
Sign up to set email alerts
|

Group versus Individualised Minimum Velocity Thresholds in the Prediction of Maximal Strength in Trained Female Athletes

Abstract: This study examined the accuracy of different velocity-based methods in the prediction of bench press and squat one-repetition maximum (1RM) in female athletes. Seventeen trained females (age 17.8 ± 1.3 years) performed an incremental loading test to 1RM on bench press and squat with the mean velocity being recorded. The 1RM was estimated from the load–velocity relationship using the multiple- (8 loads) and two-point (2 loads) methods and group and individual minimum velocity thresholds (MVT). No significant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…The inverse-linear relationship between the load lifted and movement velocity can be used to predict 1RM during various resistance training exercises [11]. Briefly, this load-velocity relationship can be modeled by assessing velocity over multiple submaximal loads (usually 3-8 loads; i.e., 'multiple-point method'), with the 1RM being estimated via linear regression as the load associated with the velocity at 1RM (i.e., the minimum velocity threshold; MVT) [12][13][14]. This relationship can also be accurately modeled using two loads (i.e., 'two-point method') [11], though the loads and MVT selected in modeling need to be considered [15].…”
Section: Introductionmentioning
confidence: 99%
“…The inverse-linear relationship between the load lifted and movement velocity can be used to predict 1RM during various resistance training exercises [11]. Briefly, this load-velocity relationship can be modeled by assessing velocity over multiple submaximal loads (usually 3-8 loads; i.e., 'multiple-point method'), with the 1RM being estimated via linear regression as the load associated with the velocity at 1RM (i.e., the minimum velocity threshold; MVT) [12][13][14]. This relationship can also be accurately modeled using two loads (i.e., 'two-point method') [11], though the loads and MVT selected in modeling need to be considered [15].…”
Section: Introductionmentioning
confidence: 99%
“…The main difference can be explained by the use of pooled data instead of individual data to calculate the regressions. Recent research showed that individual associations might result in higher accuracy than pooled data [32]. In addition, greater improvements were observed in power-oriented training [33] in ISO-load exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Another important parameter which is exercise dependent is the velocity associated with the maximal load (1RM), i.e. the minimum velocity threshold (MVT) [ 17 ]. The MVT in the back squat is approximately 0.30 m·s −1 [ 19 ], therefore displaying the minimum value of 0.10 on the scale could lead participants to underestimate submaximal and maximal loads.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the range of velocities within a scale should be exercise specific. In fact, the velocity associated with the 1RM load, called the minimum velocity threshold (MVT), is exercise specific and has been shown to differ between exercises [ 17 ]. For example in the Prone Bench Pull the MVT is about 0.50 m·s −1 [ 18 ], in the Squat about 0.30 m·s −1 [ 19 ] while in the Bench Press about 0.15 m·s −1 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%